(untitled) (The Journal of Psychology and Sociology, 2019)
In the article the influence of the "cultural shock" phenomenon on the transformation of the international programs participants meaning sphere is analyzed. The results of empirical research of meaning fields, self-consciousness and all life activities of the participants are presented before and after the international internship. The aim of the research is to reveal the specifics of influence of the “cultural shock” phenomenon on the transformation of the international programs participants meaning sphere. The Research Object: the transformation of the international programs participants meaning sphere. The Research Subject: cultural shock as the source of the transformation of the international programs participants meaning sphere. Hypothesis: the transformation of the international programs participants meaning sphere on completing their internship will be inference in: the growth of the life awareness level, stabilization of the mental condition, development of the inner world, increasing of tolerance and independence level. The Research Methods: Theoretical: analysis of scientific and psychological literature on the investigation topic; Empirical methods and techniques: A. Leotyev Test on life-meaning orientations (modified variant); G. Bazhin, N. Etkind Personality Differential (modified variant); Questionnaire on the self-assessment of psychic activation states, interest, emotional tone, tension and comfort; Questionnaire processed by the content-analysis method; The Technique of Limiting Meanings by D.A. Leontyeva; The Technique "Who am I?" by M. Kuhn, processed by the content-analysis method; 3) Methods of mathematical statistics: t - Student’s criterion, - Pearson’s criterion, criterion - Fisher’s angular transformation. The study was conducted on the basis of the S. Amanzholov East Kazakhstan State University, the city of Ust-Kamenogorsk. Under the research there were 50 people - participants of the international programs: 10 people - participants of the "Turan-Profi" program and 40 people - participants of the Work and Travel USA program. Key words: cultural shock, meaning sphere of personality, transpective analysis, intercultural adaptation.